(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2024)
This article aims to critically analyse the prohibition of prenatal adoption in Ecuador, identifying legal barriers and proposing possible legislative reforms that would allow its implementation under specific conditions. It analyses the effectiveness of the current Childhood and Adolescence Code and identifies regulatory gaps that generate legal uncertainty. The methodology used was a literature review, based on the analysis of recent scientific articles, comparative legislation and normative documents in force. The development of this work contemplates the ethical and legal dilemmas, the need to guarantee the informed consent of the pregnant mothers and the protection of the rights of the foetus. Comparison with international models shows the importance of implementing post-adoption support programmes and international cooperation to improve the transparency and effectiveness of the process. Finally, legislative reforms are proposed to create a specific framework for prenatal adoption, simplify administrative procedures, and professionalise adoption personnel.